Nichtautonome Effekte des Onkogens YAP in der Hepatokarzinogenese - Marquard, Simone; Thomann, Stefan; Weiler, Sofia Maria Elisabeth; Sticht, Carsten; Gretz, Norbert; Schirmacher, Peter; Breuhahn, Kai (Der Pathologe, 2017)
BackgroundThe transcriptional coactivator yes-associated protein (YAP) is a strong oncogene in liver cancer development.ObjectivesTo investigate if and how YAP-induced paracrine-acting factors are regulated in hepatocytes and liver cancer cells.Material and MethodsTranscriptome analysis and proteomics of murine wildtype and YAP-transgenic hepatocytes were performed to identify paracrine-acting proteins. Molecular and biochemical techniques were used to examine the mechanisms of YAP-dependent gene regulation. Gene expression data from HCC (hepatocellular carcinoma) patients was evaluated.ResultsSeveral YAP-dependent, secreted factors (e. g. CXCL10, GDF15, PDGFB) were identified. YAP regulates these factors through transcription factors of the TEAD (TEA domain) protein family. Moreover, the dysregulation of the YAP-target genes is often associated with poor HCC patient prognosis.ConclusionsYAP induces the expression of paracrine-acting factors that may affect the tumor microenvironment and therefore support carcinogenesis. This multicellular network could allow the development of novel and specific perturbation approaches.